FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN IBU NIFAS TENTANG PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS BALOI PERMAI KOTA BATAM TAHUN 2017 - Elyati, Rosana Seni; Prameswari, Yuditia (Universitas Batam, 2018)
Exclusive breast milk essential nutrients for infants, Exclusive breastfeeding is a Maternal and Infant Health Service Indicator in Puskesmas. The purpose of this research is to know the factors related to the knowledge of Nifas mother about Exclusive Breastfeeding at Baloi Permai Health Center of Batam in 2017. Analytical Research of cross sectional method, the population of all postpartum mothers who come to Puskesmas Baloi Permai in May-June 2017. The results of the study of 35 respondents good knowledge 19 respondents (54.3%), and knowledgeable less 16 respondents (45.7%), Knowledge good majority of middle-educated 9 respondents (25.7%), majority aged 25-35 years 10 respondents (28.6%), mother with gravida 2-4 people 8 respondents (22,9%). Data analysis using stastitic chi square test, there is a significant relationship between maternal knowledge with education factor, age and parity. It is expected that postpartum can follow the activities undertaken at Baloi Health Center to improve knowledge.